Digital Jihad Online Communication and Violent Extremism - Francesco Marone (Pubblicazioni ISPI, 2019)
The internet offers tremendous opportunities for violent extremists across the ideological spectrum and at a global level. In addition to propaganda, digital technologies have transformed the dynamics of radical mobilisation, recruitment and participation. Even though the jihadist threat has seemingly declined in the West, the danger exists of the internet being an environment where radical messages can survive and even prosper. Against this background, this ISPI report investigates the current landscape of jihadist online communication, including original empirical analysis. Specific attention is also placed on potential measures and initiatives to address the threat of online violent extremism. The volume aims to present important points for reflection on the phenomenon in the West (including Italy) and beyond.